Northernmost distribution of the Andean bear (Tremarctos ornatus) in South America, and fragmentation of its associated Andean forest and Paramo ecosystems - Rodríguez, Daniel; Reyes, Adriana; Gallegos-Sánchez, Silvana; Reyes-Amaya, Nicolás; Gutierrez, Jorgue; Suárez, Raúl; Prieto, Fernando (THERYA, 2019)
Current northernmost distribution of the Andean bear (Tremarctos ornatus) is not defined precisely; mentioned to be located â€œat the Serranía del Perijáâ€ without accurate/confirmed distribution records, and placed by the IUCN at the Serranía de Portuguesa (Venezuela). There is an information gap on the fragmentation of the Andean bear associated ecosystems (Andean forest and Paramo) throughout its distribution in Colombia and Venezuela. The aim of this study is to provide precise knowledge on the current northernmost distribution of the Andean bear in South America at the Serranía del Perijá, besides quantifying spatial trends of the fragmentation of its associated ecosystems at the eastern and western slopes. Confirmed distribution records were obtained from field surveys (2009 to 2016), literature, scientific collections and biodiversity databases. The fragmentation degree of Andean bear associated ecosystems was characterized using FRAGSTATS (V 4.2) software with satellite images from 2008. A current population block with at least three sectors of incidence is present along both slopes of the Serranía del Perijá. Although the Colombian slope comprises greater raw area of Andean bear associated ecosystems, it is highly fragmented and isolated. Core area analysis (extracting a disturbance buffer of 1,000 m into the border of each patch) exhibits a Venezuelan slope maintaining greater amount of Andean bear associated ecosystems at few, large and less fragmented patches. This study extends the distribution of the species 180 km until the north of the Serranía del Perijá (regarding the current distribution recognized by the IUCN) and provides the northernmost confirmed distribution records for South America: Barrancas (Colombia) and Mara (Venezuela) municipalities. This study provides the first fine-scale information on Andean bear associated ecosystems fragmentation for Colombia and Venezuela, with traceable landscape measurements permitting future long-term comparative analyses. A high fragmentation degree of the Andean bear associated ecosystems is present at the Colombian slope of the Serranía del Perijá due to extensive legal and illegal agricultural activities and wood extraction. The lack of information about the Andean bear distribution and its associated ecosystems fragmentation could be putting the survival of local populations at risk, while a clear knowledge on these issues could generate planned conservation actions by the governmental environmental authorities.